Intrabladder pressure as predictor of intraabdominal pressure in horses - De Paula, Vanessa B. [UNESP]; Canola, Paulo A. [UNESP]; Rivera, Gabriela G. [UNESP]; Filho, Dárcio Z. [UNESP]; Amaral, Gabriel P. D. [UNESP]; Ferraz, Guilherme C. [UNESP]; Ferraudo, Antǒnio S. [UNESP]; Canola, Julio C. [UNESP] (Public Library of Science (PLoS), 2019)
Objectives To investigate effects of postural changes and bladder distention on intrabladder pressure whilst estimating intra-abdominal pressure in horses. Design Two-year cohort study. Patients admitted for elective surgical procedures unrelated to gastrointestinal or genitourinary tract. Setting School of Agricultural and Veterinarian Sciences, Jaboticabal, SP, Brazil. Animals 20 adult horses, 11 males (stallions and geldings) and 9 females; between 3.5 and 12 years, weighing 350 to 500 kg. Interventions Intra-abdominal pressure was directly-recorded through abdominocentesis at the ventral midline with a fluid-filled system. Intrabladder pressure was obtained from a bladder catheter with the fluid-filled system zeroed at the level of the tuber ischia with patients in dorsal recumbency or pubic symphysis if in lateral recumbency. Measurements and main results Body position directly influenced intra-abdominal pressure. In dorsal recumbency, intraabdominal pressure differed (p < 0.05) from intrabladder pressure at end-inspiration and end-expiration regardless of whether the bladder was empty or distended. There was no correlation nor association between the two pressures in this body position. In lateral recumbency a difference (p <0.05) between intra-abdominal pressure and intrabladder pressure was recorded at end-inspiration with the bladder distended with 25 ml, and at end-expiration for distension volumes of 25 ml and 50 ml. There was a strong correlation between both pressures for left and right lateral recumbency, regardless of the distension volume. Ordinary least product (OLP) regression analysis showed no fixed or proportional bias between both pressures for distension volume of 50 ml, at both end-inspiration and end-expiration. Conclusions Indirect assessment of equine intra-abdominal pressure cannot be made in dorsal recumbency. For that purpose, patients should be in left lateral recumbency with the bladder distended with 50 ml. Values can be recorded at end-inspiration or end-expiration. Restriction Occlusion of the catheter tip by the bladder wall when minimally distended.